2008
DOI: 10.1291/hypres.31.1477
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Soy Protein Hydrolysates in N.OMEGA.-Nitro-L-Arginine Methyl Ester Hydrochloride-Induced Hypertensive Rats

Abstract: Pepsin-digested soy protein hydrolysate (SPH) has been reported to be responsible for many of the physiological benefits associated with soy protein consumption. In the present study, we investigated the effects of SPH with angiotensin-converting enzyme (ACE) inhibitory potential on blood pressure and renal injuries in rats with N -nitro-L -arginine methyl ester hydrochloride (L-NAME)-induced hypertension. Rats were fed a diet containing L-NAME (50 mg/kg body weight) with or without SPH (at 1%, 3%, or 5%) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…We observed a significant increase in serum level of potassium, with a significant depletion in sodium level in L-NAME treated rats as compared to controls. These results are different to those obtained by Yang and Chen [3] . The decrease of Na + and the increase of K + observed in this study are probably due to the generation of free radicals and the inhibition of Na + -K + ATPase pump.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We observed a significant increase in serum level of potassium, with a significant depletion in sodium level in L-NAME treated rats as compared to controls. These results are different to those obtained by Yang and Chen [3] . The decrease of Na + and the increase of K + observed in this study are probably due to the generation of free radicals and the inhibition of Na + -K + ATPase pump.…”
Section: Discussioncontrasting
confidence: 99%
“…The bioavailability depletion of this molecule contributes to the impairment of cardiovascular function which leads to the activation of the renin-angiotensin system (RAS) and consequently angiotensin II production [2] . Angiotensin II causes inflammation, production of reactive oxygen species, blood pressure elevation and may also be involved in hypertension-induced tissue damage [3] . Uncontrolled hypertension with associated endothelial damage leads to progressive renal function impairment in essential hypertension and increases cardiovascular morbidity and mortality [4] .…”
Section: Introductionmentioning
confidence: 99%
“…43 An earlier study also indicates that anti-hypertensive and renoprotective effects of protective agents in nitric oxide (NO)-deficient rats might be mediated via its ACE inhibitory activity. 44 Strikingly, the adverse effect of the safe dose of BPA on oxidative stress, nitric oxide metabolism, and vasoactive factors that played crucial role in cardiovascular physiology was observed only under hypertensive milieu which requires further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Given that CKD is a prototypical example of progressive fibrosis leading to organ failure [33], it is not surpising that the renoprotective effects of soy correlate with reduced fibrosis. In animal models [15,34], and clinical studies [19,35,36], soy has been shown to have an anti-inflammatory impact, including a reduction in NF-kB activity [15,16]. Given the emerging link between inflammation and renal fibrosis [37], this suggests that the anti-inflammatory effect of soy may underlie the reduction in fibrosis observed.…”
Section: Discussionmentioning
confidence: 99%